Distributed generation modelling for unbalanced three-phase power flow calculations in smart grids - Gallego, Luis A. [UNESP]; Carreno, Edgar; Padilha-Feltrin, Antonio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Distributed Generators (DG) are generally modeled as PQ or PV buses in power flow studies. But in order to integrate DG units into the distribution systems and control the reactive power injection it is necessary to know the operation mode and the type of connection to the system. This paper presents a single-phase and a three-phase mathematical model to integrate DG in power flow calculations in distribution systems, especially suited for Smart Grid calculations. If the DG is in PV mode, each step of the power flow algorithm calculates the reactive power injection from the DG to the system to keep the voltage in the bus in a predefined level, if the DG is in PQ mode, the power injection is considered as a negative load. The method is tested on two well known test system, presenting single-phase results on 85 bus system, and three-phase results in the IEEE 34 bus test system. © 2011 IEEE.
Keywords: Distributed Generation; Distribution systems; modeling; power Flow; Bus systems; DG unit; Distributed generators; Operation mode; Power flow algorithm; Power flow calculations; Power flow studies; Power injection; Reactive power injections; Smart grid; Test systems; Three-phase power flow; Distributed power generation; Mathematical models; Reactive power; Smart power grids